Bioprospecção de bactérias endofíticas como agentes de biocontrole da mancha de Exserohilum turcicum e como promotoras do crescimento de plantas de milho (Zea mays L.) - Shiomi, Humberto Franco [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
Doenças de diversas naturezas e etiologias acometem a cultura do milho. O controle dos fitopatógenos, na maioria das vezes, é realizado através de cultivares resistentes e/ou pulverizações com fungicidas, cuja utilização indiscriminada resulta em uma série de problemas, como a contaminação ambiental, dos alimentos e dos consumidores, no aparecimento de populações resistentes de patógenos e na diminuição de populações de organismos benéficos ou não-alvos. Nesse contexto, os microrganismos endofíticos aparecem como ferramentas de controle biológico de pragas e doenças. Eles compreendem, principalmente, fungos e bactérias que habitam o interior das plantas sem causar, aparentemente, danos aos seus hospedeiros. Sua capacidade de biocontrole pode advir de vários mecanismos, como a produção de substâncias deletérias a fitopatógenos ou competindo por espaço e nutrientes. Indiretamente, induzindo resistência sistêmica no hospedeiro ou pela produção de substâncias promotoras de crescimento. No presente...

Diseases of several natures and etiologies affect the cultivation of maize. The control of plant pathogens, in most cases, is realized by resistant cultivars and/or spraying with fungicides, whose indiscriminate use results in a series of problems such as environmental contamination, food and consumers, the emergence of resistant populations of pathogens and the decrease in populations of beneficial organisms or non-targets. In this context, the endophytes appear as tools for the biological control of pests and diseases. They include, principally, fungi and bacteria that inhabit the inside of plants without cause, apparently, damage to their hosts. His ability to biocontrol may arise from various mechanisms, such as the production of deleterious substances to the plant pathogens or competing for space and nutrients. Indirectly, inducing systemic resistance in the host or by plant-growth promoting. In the present work, 95 maize endophytes strains and a strain of Bacillus subtilis 0G; Bacillus lentimorbus and Streptomyces sp. were individually tested in vitro and in vivo conditions, on the antagonism to several fungi plant pathogens and in control of the Exserohilum turcicum leaf spot under greenhouse conditions, by the seed microbiolization and by spraying the aerial part of the plants, 72 and 24 hours before and on the same day of the inoculation of the pathogen. It was also tested, ...(Complete abstract click electronic access below)
Keywords: Pragas - Controle biologico; Bacterias; Milho; Endophytes; Maize; Exserohilum turcicum; Biological control